Multiplexing in Multi-Reflecting TOF MS - Verenchikov, Anatoly; Kirillov, Sergey; Khasin, Yury; Makarov, Vasily; Yavor, Mikhail; Artaev, Viatcheslav (Journal of Applied Solution Chemistry and Modeling, 2016)
The paper presents an overview of original inventions, development and experimental results by the group of authors in the area of multi-reflecting time-of-flight mass spectrometry with Folded Flight Path (FFP®) (MR-TOFMS) with main focus on multiplexing methods for improving the analysis throughput, i.e. the amount of information per time unit. MR-TOF provides panoramic spectra (virtue of TOFMS), while significantly enhancing resolving power, thus, providing yet more information. Resolving power R=500,000 is demonstrated to resolve isobars and to improve mass accuracy to sub-ppm level. Encoded Frequent Pulsing (EFPTM) method improves sensitivity, expands dynamic range and opens multiple incarnations of parallel and fast tandem methods of analysis based on using ion traps, TOFMS and ion mobility for rapid and lossless parent ion separations.